2017
DOI: 10.1016/j.anai.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of altered gut microbiota composition with chronic urticaria

Abstract: The results reveal a change of frequency and relative amounts of A muciniphila, C leptum, and F prausnitzii in patients with CU compared with healthy controls. This is the first study, to our knowledge, to show the change of microbiota composition in patients with CU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 61 publications
(57 reference statements)
3
45
1
1
Order By: Relevance
“…At the genus level, members of the Bacteroides, Faecalibacterium, Bifidobacterium, Lactobacillus, and unidentified Ruminococcaceae were relatively lower and members of unidentified Enterobacteriaceae were relatively increased compared to healthy controls, which is partly consistent with previous studies about CU or allergic diseases (Sjogren et al, 2009;Johansson et al, 2011;Candela et al, 2012;Nabizadeh et al, 2017;Rezazadeh et al, 2018;Chiu et al, 2019). For example, Nabizadeh et al (2017) and Rezazadeh et al (2018) reported a depletion in the relative amounts of Faecalibacterium prausnitzii, Clostridia, Akkermansia muciniphila, Bifidobacterium, and Lactobacillus in CU patients. The mean of the relative amounts of Enterobacteriaceae was increased.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the genus level, members of the Bacteroides, Faecalibacterium, Bifidobacterium, Lactobacillus, and unidentified Ruminococcaceae were relatively lower and members of unidentified Enterobacteriaceae were relatively increased compared to healthy controls, which is partly consistent with previous studies about CU or allergic diseases (Sjogren et al, 2009;Johansson et al, 2011;Candela et al, 2012;Nabizadeh et al, 2017;Rezazadeh et al, 2018;Chiu et al, 2019). For example, Nabizadeh et al (2017) and Rezazadeh et al (2018) reported a depletion in the relative amounts of Faecalibacterium prausnitzii, Clostridia, Akkermansia muciniphila, Bifidobacterium, and Lactobacillus in CU patients. The mean of the relative amounts of Enterobacteriaceae was increased.…”
Section: Discussionsupporting
confidence: 89%
“…We previously conducted an epidemiologic investigation and found relevant evidence linking gut microbiota and CSU. Several studies have suggested that the changes in gut microbiota composition are linked to CU, including Akkermansia muciniphila, Faecalibacterium prausnitzii, the Clostridium leptum group, the Enterobacteriaceae family (Nabizadeh et al, 2017), and the Lactobacillus, Bifidobacterium, and Bacteroides genera (Rezazadeh et al, 2018); however, there is no specific mechanism by which to explore the dysbiosis of gut microbiota in the pathogenesis of CSU.…”
Section: Introductionmentioning
confidence: 99%
“…More recent work has shown an increased frequency of dysbiosis of the gastrointestinal tract in CSU. As such there was a significantly reduced frequency of Akkermansia muciniphila , Clostridium leptum and Faecalibacterium prausnitzii in the stools of CSU patients while that of Enterobacteriaceae was unchanged [50]. Intriguingly, the number of tryptase and CD117 positive mast cells per high power field were significantly higher in patients with CSU compared to controls and adjunctive treatment with mast cell stabilisers has been suggested [51].…”
Section: Aetiological and Associated Factors In Csumentioning
confidence: 99%
“…Some patients with AU may turn into CU though the treatment protocol is the same. Compared to AU, CU is a more complex disease that may relate to imbalances in immunity, inflammation, and coagulation [2]. Although extensive studies have been done, the pathogenesis of CU is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Whether intestinal flora imbalance results in the susceptibility to CU, few reports demonstrated it. Recently, the changes in bacterium Akkermansia muciniphila , Faecalibacterium prausnitzii , Clostridium leptum , and Enterobacteriaceae were reported in CU patients [2]. Unfortunately, the whole intestinal microbiome in CU patients is rarely being clarified.…”
Section: Introductionmentioning
confidence: 99%